Dramatic Gamification in Bassim Altayeb’s Izayza - Algburi, Maryam; Naser, Alyaa (Al-Adab Journal, 2024)
This paper delves into gamification, or the use of game elements in non-gaming environments. This paper Reflects on the existing game elements in Izayza by Bassim Altayeb while aiming to show the influence of those elements and how this play carries itself in terms of balancing the resulting emotions and thoughts that the reader/the audience gets. It also revolves around how Izayza incorporates gamification to create an experimental environment for its spectators in coordination with the message of the play. The play’s unique integration of the audience into the performance, blurring the lines between actors and viewers, reinforces its gamified nature. While maintaining a serious tone, Izayza aligns with the concept that playing and the dramatic arts are not mutually exclusive, providing a thought-provoking and immersive experience for its participants. Lastly, this intersection suggests a relationship between games and drama.